PERAN GURU DAN ORANG TUA DALAM PENANGANAN ANAK DENGAN KECENDERUNGAN HIPERAKTIF USIA 4-5 TAHUN DI TKIT NURUL ILMI, NGEMPLAK, BOYOLALI - Kadarsi, Rusmiyati Siti (LPPM STKIP PGRI Bandar Lampung, 2021)
The purpose of the study is to determine the role of teachers and parents in handling hyperactivity child behavior aged 4-5 years. This study is also to know the importance of cooperation between teachers and parents in assisting hyperactive children. Descriptive qualitative methods is used in this study. The data collecting technique are observation, interviews and documentation. The results show that the importance of the role of the teachers in recognizing, understanding the characteristics of hyperactive children and accompanying the learning and socializing process of children in class based on emotional, cognitive, and social aspects. In addition, the role of parents in providing attention, affection, also learning assistance at home. As well as providing opportunities for children with hyperactive tendencies to interact with the environment. The pattern of cooperation between teachers and parents is also realized by always coordinating and providing information about children’s development. Puzzle games are given as a means to train children’s focus.